Factors associated with low life life satisfaction in community-dwelling elderly: FIBRA Study - Juliana Martins Pinto; Anita Liberalesso Neri (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2013)
The objectives were to identify factors associated with decreased life satisfaction in community-dwelling elderly and describe such factors according to gender and age bracket. The study interviewed 2,472 elderly individuals 65 years or older without cognitive deficits suggestive of dementia, in probabilistic samples from seven Brazilian cities. All measures were self-reported except for functional performance, indicated by handgrip and gait speed. Women had more chronic diseases, worse functional performance, and greater social involvement when compared to men. The oldest participants showed worse functional performance and less social involvement when compared to the youngest. Low satisfaction was associated with three or more diseases, memory problems, low social involvement, low handgrip strength, and urinary incontinence. The authors conclude that health, functional performance, and social involvement interact with well-being, so interventions targeting these areas can favor quality of life for the elderly.